Examination of Transport Performance and Authenticity on Behavioural Intention - Handayani, Bintang; Rashid, Basri (UI Scholars Hub, 2021)
This study aims to scrutinise the transport performance and authenticity as one of the elements in tourism attributes in relation with behavioural intention. Utilising quantitative approach; data collected from survey of 384 overseas tourists were used to clarify the research proposition. The study suggests that transport performance may emerge as one of organic image elements for destination brand identity formation, influences cognitive image of overseas tourist but insignificant on tourist’s behavioural intention. In addition, future spectrum of the transport development in relation with authenticity indicates its importance for not damaging the destination’s overall profile.